Synthesis and characterization of zinc- and magnesium- aluminium layered double hydroxide nanocomposite intercalated with sodium dodecyl sulfate - Babakhani, Samaneh (2014)
The co-precipitation method was employed to prepare Zn/Al–NO3–LDH and Mg/Al–NO3–LDH at molar ratios of Zn2+/Al3+ and Mg2+/Al3+ of 2, 3 and 4. The pH was fixed at 7 for Zn/Al-LDH samples and 10 for Mg/Al–LDH samples. Sodium dodecyl sulfate (SDS) was intercalated to Zn/Al–LDH and Mg/Al–LDH to form a new organic–inorganic nanocomposite (LDH–SDS). The concentration of SDS solution used was 0.2 M, 0.4 M and 0.8 M in different molar ratio, Zn2+/Al3+ and Mg2+/Al3+= 2, 3 and 4 at pH =10. The structural, textural, optical, thermal and morphological properties of the resultant nanocomposites were investigated. Electron spin resonance (ESR) spectra of samples were also studied. Analysis of the XRD spectra of LDH and LDH-SDS samples showed that the crystallite size was in the range of 23–51 nm for Zn/Al series and 7-44 nm for Mg/Al series, which confirmed that the pure and intercalated LDH were nanocomposite. This is corroborated by the results of unit cell parameters (a and c) which showed that the construction of LDH resulted in nanolayers. The shifting in the basal spacing for LDH–SDS samples to around 2.52–2.60 nm comparing with 0.79 nm for Mg/Al–NO3–LDH and 2.54–2.61 nm comparing with 0.89 nm for Zn/Al–NO3–LDH indicated the SDS intercalation within the galleries. Optical band gap of the samples was calculated using Kubelka-Munk model from UV-Vis-NIR Diffuse reflectance spectroscopy. Due to the presence of different phases in LDH, more than one energy gaps were obtained in diffuse reflectance spectroscopy of the samples for LDH and LDH–SDS samples. The values of Eg1 and Eg2 were found around 4.8 eV and 3.75 eV for Zn/Al and MgrAl–LDH (r 2, 3 and 4) which can be attributed to the presence of NO3− groups in the LDH interlayer. For MgrAl–LDH–SDS samples with different concentration of SDS and molar ratio (r 2, 3 and 4), the values of Eg1 and Eg2 were observed to increase to around 5.2 eV and 4.1 eV. Consequently, for ZnrAl–LDH–SDS samples in different concentration of SDS, the band gap energy of Eg1 and Eg2 were found to increase to 5.2 eV and 4.1 eV for r = 2 and 5.1 eV and 3.9 eV for r = 3. When r = 4, Eg1 and Eg2 were decreased to 4.3 eV and 3.2 eV for LDH–SDS with 0.2 M of SDS. For LDH–SDS with 0.4 M and 0.8 M of SDS, only one energy gap at around 3.23 eV was observed. These Eg values can be due to the electronic transition of the oxygen from the DS anion (SO42-) from the interlayer and a nearby Al nucleus (I = 5/2) from the LDH sheets. The electron spin resonance (ESR) spectra of LDH were comprised of a broad signal with g-factor between 1.9323 and 2.0187 for MgrAl-LDH and g-factor between 2.06841 to 2.11875 for ZnrAl–LDH which can be caused by the existence of nitrate radicals within LDH interlayer. The ESR spectra of LDH-SDS are observed due to the interaction between a SO42- radical from DS anion and a nearby Al nucleus (I = 5/2) from the LDH sheets. ESR results for Zn/Al–LDH–SDS samples revealed that the g-factor was decreased comparing with LDH samples. The obtained results for Mg/Al-LDH-SDS samples demonstrated that the g-factor was observed to increase for ratio 2, while it was found to decrease for ratio 3 and 4.